Procrastination, its antecedents and its organisational outcomes among employees in the public sector in Istanbul. (26th February 2020) - Bilginoğlu, Elif; Yalçıntaş, Murat
This study investigates the phenomenon of the tendency to procrastinate with its three triggers: time management, perfectionism, and fear of failure as well as its organisational outcomes which are higher job stress and lower job satisfaction. Parametric tests and path analysis were performed to analyse the relationship between the variables in the model. The results revealed that poor time management (time wasting and deficient time efficiency), discrepancy and fear of failure are causes of procrastination in organisations and the employees, who procrastinate, report a higher job stress and a lower job satisfaction.